Bile cast nephropathy (cholemic nephropathy) associated with hepatitis A-induced acute liver failure and haemolysis in a patient with glucose-6-phosphate dehydrogenase deficiency - Ali Hamdan; Johny Salem; Karam Karam; Maria Ziadeh; Pierre Hani (European Journal of Case Reports in Internal Medicine)
Introduction: The hepatitis A virus (HAV) is a common cause of acute hepatitis, while glucose-6-phosphate dehydrogenase (G6PD) deficiency is a widespread enzyme disorder that predisposes individuals to haemolysis and hyperbilirubinemia. We report a case of a G6PD-deficient patient with hepatitis A-induced acute renal failure (ARF), highlighting the role of plasmapheresis and haemodialysis in management. Case description: A 40-year-old male with G6PD deficiency and hypertension was transferred for further care after presenting with fever, diarrhoea and jaundice. Laboratory results showed severe haemolysis and elevated bilirubin (70 µmol/l); hepatitis A serology was positive. The patient developed acute liver failure and ARF, with creatinine reaching 7.3 mg/dl. Plasmapheresis and haemodialysis were initiated, leading to stabilisation of renal function and a significant decrease in bilirubin by six weeks post-discharge. Discussion: G6PD deficiency increases the risk of haemolysis, especially during infections such as hepatitis A. This can lead to severe hyperbilirubinemia and complications including bile cast nephropathy. In this case, plasmapheresis effectively reduced bilirubin and inflammatory mediators, while haemodialysis addressed renal dysfunction. Together, these therapies were crucial in stabilising renal function. Conclusion: Bile cast nephropathy is an important cause of kidney injury in severe hyperbilirubinemia. This case highlights the effectiveness of plasmapheresis and haemodialysis in managing the condition and supporting renal recovery, especially in the absence of established treatment guidelines.